Аналіз дисипативних структур на основі варіаційного принципу Гаусса - Гафійчук, В.В.; Лубашевський, І.О. (Український математичний журнал, 1992)
Для нахождения решений диссипативных систем предложен вариационный принцип Гаусса. На примере системы двух уравнений реакции-диффузии найдены приближенные решения в виде автосолитонов и периодических диссипативных структур. The Gauss variational principle is suggested as a method of finding the solutions of dissipative systems. Using as an example a system of two reaction-diffusion equations, approximate solutions are found for the case of auto-solitons and periodic dissipative structures.